Accommodating the cost of growth and swimming in fish—the applicability of exercise-induced growth to juvenile hapuku (Polyprion oxygeneios) - Khan, Javed R.; Trembath, Caroline; Pether, Steve; Bruce, Michael; Walker, Seumas P.; Herbert, Neill A. (Frontiers in Physiology, 2014)
Induced-swimming can improve the growth and feed conversion efficiency of finfish aquaculture species, such as salmonids and Seriola sp., but some species, such as Atlantic cod, show no or a negative productivity response to exercise. As a possible explanation for these species-specific differences, a recent hypothesis proposed that the applicability of exercise training, as well as the exercise regime for optimal growth gain (ER opt growth), was dependent upon the size of available aerobic metabolic scope (AMS). This study aimed to test this hypothesis by measuring the growth and swimming metabolism of hapuku, Polyprion oxygeneios, to different exercise regimes and reconciling the metabolic costs of swimming and growth (i.e. specific dynamic action, SDA) against AMS. Two 8-week growth trials were conducted with ERs of 0.0, 0.25, 0.5, 0.75, 1 and 1.5 body lengths per second (BL s-1). Fish on a relatively high growth trajectory showed a small but positive growth response to exercise but only in the range of 0.5 to 0.75 BL s-1 compared to static water controls. Slightly larger fish on a slower growth trajectory, however, showed no evidence of exercise-induced growth. Long-term exposure to water flow at 0.75 and 1.5 BL s-1 also yielded no difference in the swimming metabolism of fish relative to static water controls. Reconciling the SDA of hapuku with the metabolic costs of swimming showed that hapuku AMS is sufficient to support growth and swimming at all ERs. The current study therefore suggests that exercise-induced growth is independent of AMS and possibly varies as a function of species, life stage and/or inherent growth trajectories.